La cadena de valor del cacao y su impacto socio económico en los productores asociados de la empresa KAACAO S.A. - Velásquez Velásquez, Lorena Annabel (2025)
This research evaluated the cocoa value chain and its socioeconomic impact on the affiliated producers of the company Kaacao S.A., with the aim of improving the organization’s internal processes. A quantitative methodological approach was adopted, allowing for a comprehensive diagnosis of the current situation. The study involved an extensive literature review and field research through structured surveys adapted from a 2019 study by INIAP. These surveys focused on key aspects related to the producers’ socioeconomic conditions and operational activities within the value chain. For data analysis, the Kolmogorov-Smirnov normality test and Pearson correlation analysis were applied to identify significant relationships between relevant variables. During the diagnostic and improvement proposal phase, management tools such as the Ishikawa diagram were used to identify root causes, the Pareto diagram to prioritize the most critical factors, and the 5W+1H matrix to structure clear and feasible solution strategies. In conclusion, the study revealed substantial opportunities for improvement in internal processes, contributing to enhanced competitiveness and sustainability of the cocoa value chain, with direct benefits for the associated producers.